2016
DOI: 10.1007/s40496-016-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of Dental Ceramics to Titanium: Processing and Conditioning Aspects

Abstract: Difficulties related to titanium processing (casting) and the problematic titanium-ceramic bond have been limiting the latter's application in prosthetic dentistry for many years. Recent advances in subtractive and additive CAD/CAM technologies have provided alternative routes for titanium processing. The effect of a processing route on titanium surface characteristics and on the strength of its bond to porcelain need to be assessed, since most paths for enhancing porcelain bonding involve preparation of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 85 publications
(102 reference statements)
1
10
0
Order By: Relevance
“…The recorded 10-nm thickness of the oxide is in agreement with that reported for the thickness of the passive oxide scale [28]. This layer is known to be stable and self-limiting, protecting the metal from further oxidation and acting as an effective barrier against metal dissolution and the release of ions [2,28]. At elevated temperatures, however, oxygen diffuses through the originally formed oxide layer and reaches the metal/oxide interface, reacting with the titanium to form titanium oxides.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The recorded 10-nm thickness of the oxide is in agreement with that reported for the thickness of the passive oxide scale [28]. This layer is known to be stable and self-limiting, protecting the metal from further oxidation and acting as an effective barrier against metal dissolution and the release of ions [2,28]. At elevated temperatures, however, oxygen diffuses through the originally formed oxide layer and reaches the metal/oxide interface, reacting with the titanium to form titanium oxides.…”
Section: Discussionsupporting
confidence: 89%
“…Porcelain-fused-to-metal (PFM) fixed dental prostheses (FDPs) are widely used in prosthetic dentistry, providing reliable, long-term clinical outcomes by combining the good mechanical properties of the metal framework and the favorable aesthetics of veneered porcelain [1]. The PFM concept relies on the formation of a strong and durable metal-ceramic bond, which can be a challenging procedure [2]. It has been shown that four mechanisms contribute to the metal-ceramic bonding: chemical bonding, mechanical interlocking, van der Waal's interactions, and the porcelain's exposure to residual compression on cooling from the firing temperatures due to the slightly lower coefficient of thermal expansion (CTE) of the porcelain than that of the metal [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface roughening by abrasion with airborne Al 2 O 3 particles has been widely accepted as a standard operating procedure for bond enhancement in clinical practice. 9,32,33 It promotes mechanical retention between the metal and the ceramics. 9,30,31 Furthermore, airborneparticle abrasion also removes gross surface irregularities and cleans the investment material from the surface of the cast alloys.…”
Section: Discussionmentioning
confidence: 99%